Dispersal potential index (DPi) as alternative indicator for coral larvae dispersal potential - Mohd Hanapiah, Muhammad Faiz; Saad, Shahbudin; Ahmad, Zuhairi; Mustapa, Mohd Zaini (UCTS Publishe, 2021)
Dispersal of coral larvae is influence by combination of multiple factors, yet comparisons are commonly displayed on two- or three-dimensional charts (i.e.: pelagic larvae duration vs. distance). Therefore, the present study implies the application of Dispersal Potential Index (DPi) based on the factors which influence the dispersal range and potential such as pelagic larvae duration (PLD), adult coral cover, current speed and depth variations. Each factor was given score from 1 to 10 based on their influence towards dispersal potential. The DPi was able to describe dispersal potential of Acropora larvae from two separated reef sites (Bidong Island and Kuantan Coastal Waters) which share common hydrodynamic pattern. It is suggested that Acroporid larvae in Kuantan coastal waters has greater dispersal potential than Bidong Island. DPi for Kuantan coastal waters was classified as intermediate dispersal range while DPi and Bidong Island was categorized as short dispersal range. This approach is arguably the first of its kind in describing the multiple factors for dispersal of coral larvae. The application of DPi is important especially for reef managers to estimate dispersal range of coral for a better marine ecosystem management.